2021
DOI: 10.3390/life11111251
|View full text |Cite
|
Sign up to set email alerts
|

Promoter Demethylation Upregulates STEAP1 Gene Expression in Human Prostate Cancer: In Vitro and In Silico Analysis

Abstract: The Six Transmembrane Epithelial Antigen of the Prostate (STEAP1) is an oncogene overexpressed in several human tumors, particularly in prostate cancer (PCa). However, the mechanisms involved in its overexpression remain unknown. It is well known that epigenetic modifications may result in abnormal gene expression patterns, contributing to tumor initiation and progression. Therefore, this study aimed to analyze the methylation pattern of the STEAP1 gene in PCa versus non-neoplastic cells. Bisulfite amplicon se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 42 publications
1
3
0
Order By: Relevance
“…In linear correlation, negative relationships were examined between STEAP1 and several cancers such as BRCA, PRAD, SKCM, and UCEC but positive connections in COAD and LUSC. Consistent with a previous study, STEAP1 was downregulated in prostate cancer tissues compared with normal samples and negatively associated with promoter methylation levels integrating both vitro and silico analysis [38].…”
Section: Discussionsupporting
confidence: 91%
“…In linear correlation, negative relationships were examined between STEAP1 and several cancers such as BRCA, PRAD, SKCM, and UCEC but positive connections in COAD and LUSC. Consistent with a previous study, STEAP1 was downregulated in prostate cancer tissues compared with normal samples and negatively associated with promoter methylation levels integrating both vitro and silico analysis [38].…”
Section: Discussionsupporting
confidence: 91%
“…However, it is unclear whether the loss of tumor STEAP1 expression is solely due to inherent tumor antigen heterogeneity or whether there is also adaptive downregulation of STEAP1 expression. A recent publication showed that promoter methylation of STEAP1 modulates STEAP1 expression and epigenetic deregulation by DNA methyltransferase and histone deacetylase inhibition was sufficient to significantly upregulate STEAP1 expression 73 . Treatment with epigenetic inhibitors in combination with STEAP1 CAR T cell therapy could simultaneously enhance tumor STEAP1 expression and reprogram CAR T cells to favorable exhaustionresistant differentiation states 74,75 , thereby mitigating tumor antigen loss and enhancing antitumor efficacy in prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is unclear whether the loss of tumor STEAP1 expression is solely due to inherent tumor antigen heterogeneity or whether there is also adaptive downregulation of STEAP1 expression. A recent publication showed that promoter methylation of STEAP1 modulates STEAP1 expression and epigenetic deregulation by DNA methyltransferase and histone deacetylase inhibition was sufficient to significantly upregulate STEAP1 expression 57 . Perhaps treatment with epigenetic inhibitors in combination with STEAP1 CAR T cell therapy could simultaneously enhance tumor STEAP1 expression and reprogram CAR T cells to favorable exhaustion-resistant differentiation states 58, 59 , thereby mitigating tumor antigen loss and enhancing antitumor efficacy in prostate cancer.…”
Section: Discussionmentioning
confidence: 99%